Short-term Forecasting for Direct Normal Irradiance with Numerical Weather Prediction Models in Alentejo - Lopes, Francisco (2019)
Assessment of DNI short-term forecasts in southern Portugal with predictions from the ECMWF against measurements. Use of forecasts in a power simulation model (SAM) for operation management of CSP systems.